Predicting mixing free energy using mutual ghosting. Issue 11 (19th August 2022) - Shetty, Shreya; Agarwala, Puja; Gomez, Enrique D.; Milner, Scott T.
Abstract : Weakening interactions in a miscible blend induces demixing; the corresponding thermodynamic work can be integrated, and the free energy of the resulting interface measured. Combining these results gives the mixing free energy. Abstract : The excess free energy of mixing Δ G ex governs the phase behavior of mixtures and controls material properties. It is challenging, however, to measure Δ G ex in simulations. Previously, we developed a method that combines molecular dynamics (MD) simulations with thermodynamic integration along the path of transformation of chains to predict the Flory Huggins interaction parameter χ for polymer mixtures and block copolymers. However, this method is best applied when the constituent molecules of the blends are structurally related. To overcome this limitation, we have developed a new method to predict Δ G ex for mixtures. We perform simulations to induce phase separation within a mixture by gradually weakening the interaction between different species. To compute Δ G ex we measure the thermodynamic work required to modify the interactions and the interfacial energy between the separated phases. We validate our method by applying it first to equimolar mixtures of labeled and unlabeled Lennard-Jones (LJ) beads, and labeled and unlabeled benzene, which results in good agreement with ideal solution theory. Then we compute the excess free energy of mixing for equimolar mixtures of benzene and pyridine, using both united-atom (UA) and all-atom (AA) potentials. Our results using UA potentials predict a value for Δ G ex about four times the experimental value, whereas using AA potentials gives results consistent with experiment, highlighting the need for good potentials to faithfully represent mixture behavior.